1996
DOI: 10.1079/bjn19960198
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of methylmalonic acid caused by vitamin B12-deficiency disrupts normal cellular metabolism in rat liver

Abstract: To clarify the relationship between intracellular concentrations of methylmalonic acid and metabolic and growth inhibition in vitamin B,,deficient rats, hepatic methylmalonic acid levels were assayed and inhibition of glucose and glutamic acid metabolism by methylmalonic acid was studied in isolated hepatocytes. Vitamin B,,deficient rats (14 weeks old) excreted more urinary methylmalonic acid and had lower body weights than the control rats. Hepatic methylmalonic acid levels (3-6 (SD 1.30)-5.3 (SD 0.51) pmol/g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…In addition, methylmalonic acid is produced by the hydrolysis of methylmalonyl-CoA, accumulated in the plasma and tissues, and excreted abnormally into the urine (methylmalonic aciduria) (1,2,16). It has been reported that methylmalonic acid, when accumulated in the liver, decreases respiratory activity by inhibiting the succinate dehydrogenase reaction (2, 7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, methylmalonic acid is produced by the hydrolysis of methylmalonyl-CoA, accumulated in the plasma and tissues, and excreted abnormally into the urine (methylmalonic aciduria) (1,2,16). It has been reported that methylmalonic acid, when accumulated in the liver, decreases respiratory activity by inhibiting the succinate dehydrogenase reaction (2, 7).…”
Section: Resultsmentioning
confidence: 99%
“…In mammals under Cbl-deficient conditions, methionine synthase and methylmalonyl-CoA mutase activities are greatly lowered due to the defect in their coenzymes, MeCbl and AdoCbl, and hematological and neurological abnormalities and growth retardation are induced (1)(2)(3).…”
Section: Abnormal Increase In the Expression Level Of Proliferating Cmentioning
confidence: 99%
“…Disorders of Cbl metabolism may affect mitochondrial (mt) functions. Methylmalonyl and propionic acid accumulation has been claimed to cause a reduction of pyruvate dehydrogenase, succinate dehydrogenase and succinyl‐CoA ligase activities and a reduction in cell ATP content [3–6]. The energetic metabolism might also be impaired by the accumulation of saturated and unsaturated monocarboxylic fatty acids, as a result of ketotic episodes of organic acidemia [7].…”
Section: Introductionmentioning
confidence: 99%
“…18 Thus, holo-MCM activity was very low during B 12 deficiency and then significant accumulation of MMA occurs in the cells. 47 MMA is a potent inhibitor of succinate dehydrogenase (EC 1.3.99.1) that participates in both the TCA cycle and respiratory chain. 48 Thus, MMA increase due to B 12 deficiency blocks the mitochondrial respiration and consequently disrupts various metabolic pathways.…”
Section: Vitamin B 12 Deficiencymentioning
confidence: 99%